Seasonal heat storage in calcium sulfoaluminate based hardened cement pastes – experiences with different prototypes. (October 2019) - Kaufmann, Josef; Winnefeld, Frank
Highlights: Hydration/dehydration of ettringite is applied for seasonal storage of solar heat. Calcium sulfoaluminate cement is used to make ettringite-based storage elements. A full scale prototype was incorporated in a residential house. Loading and deloading was successfully performed. Further optimization of operational conditions are proposed. Abstract: Seasonal storage of excess solar energy is a key factor for the enhancement of the energy performance of a decentralized energy supply of private homes. Furthermore, thermal heat storage allows to bridge demand or supply gaps and is thought to be an important element to increase the flexibility of future renewable energy supply systems. Cementitious materials, being widely available, cheap construction materials, have been proposed for thermal heat storage based on the utilization of their relatively high specific heat capacity. Seasonal heat storage in concrete or mortar has been achieved solely by the incorporation of phase change materials (PCM). In this contribution, special hardened cement pastes based on hydrated calcium sulfoaluminate cements (CSA), containing large amounts of ettringite as main hydrate phase, are proposed as seasonal heat storage material. Combining relatively high storage capacity and moderate loading temperatures (<100 °C) with mechanical performance and low cost they possess significant advantages regarding the application in buildings. Theoretical ettringite content of fully hydrated blends based on CSA-OPC-gypsum was modeled and based on these results the thermal properties of some variants were studied. Furthermore, hygric characteristics, microstructure, mechanical and thermo-physical properties were derived. Different prototypes made with CSA-based hardened cement pastes as seasonal storage material ranging from small size to large scale are studied. Construction details and temperature and humidity distributions within a modular 6 m 3 ettringite heat storage unit during loading and deloading are presented.